2015
DOI: 10.1039/c4rp00241e
|View full text |Cite
|
Sign up to set email alerts
|

Measuring understanding of nanoscience and nanotechnology: development and validation of the nano-knowledge instrument (NanoKI)

Abstract: aAs the application of nanotechnology in everyday life impacts society, it becomes critical for citizens to have a scientific basis upon which to judge their perceived hopes and fears of 'nano'. Although multiple instruments have been designed for assessing attitudinal and affective aspects of nano, surprisingly little work has focused on developing tools to evaluate the conceptual knowledge dimension of public understanding. This article reports the validation of an instrument designed to measure conceptual k… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
16
0
3

Year Published

2016
2016
2023
2023

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(20 citation statements)
references
References 41 publications
1
16
0
3
Order By: Relevance
“…It is also thought to be effective for teachers to be literate in biotechnology prior to starting their service so that they can effectively communicate their skills to students because implementations of teaching are being supported by their previous formal and informal education . In addition, the test developed within this study is broader in scope, applicable, and easier to score than other measurement tools in other studies .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It is also thought to be effective for teachers to be literate in biotechnology prior to starting their service so that they can effectively communicate their skills to students because implementations of teaching are being supported by their previous formal and informal education . In addition, the test developed within this study is broader in scope, applicable, and easier to score than other measurement tools in other studies .…”
Section: Discussionmentioning
confidence: 99%
“…When studies on biotechnology are examined in regard to prospective teachers, studies on the prospective teachers' attitudes toward biotechnology , teachers' beliefs about biotechnology , teachers' perceptions about the risks of biotechnology, and teachers' knowledge levels regarding biotechnology are found. Also, Schönborn, Höst and Palmerius have developed an instrument to measure conceptual knowledge of nanoscience and nanotechnology in their work. In these studies, biotechnology literacy is addressed in terms of a single dimension, and the measurement tools used to determine biotechnology literacy are insufficient.…”
Section: Introductionmentioning
confidence: 99%
“…NanoSim was designed to integrate twenty core concepts that our research has shown to be fundamental to understanding nano (Schönborn et al 2015). Within NanoSim-PC, these concepts are included as concise conceptual statements and accompanying visuals that can be accessed through information icons (represented as purple disks embedded in the nanoscenarios).…”
Section: Nanosim-pc In Teaching About Nanoscience and Technologymentioning
confidence: 99%
“…Citizens have no firm foundation for understanding NST due to the many conceptual challenges, e.g. concerning relative size of the nanoscale and nanoscale interactions (Schönborn, Höst, & Lundin Palmerius, 2015). This state of affairs has aroused some concerns, since it is likely that in the near future, citizens will have to make more and more decisions on NST-related issues -both at the personal level, as consumers, and also at the societal level (Jones, Blonder, Gardner, Albe, Falvo, & Chevrier, 2013).…”
Section: Introductionmentioning
confidence: 99%